(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
This paper presents the results of research conducted within R&D project. The primary goal was to apply the current state of the art technology in aluminium to a timber-based frames, but also to improve the energy performance of the building envelope and create environmentally friendly product, which physical, structural and aesthetic performances are equal to or even better than equivalent aluminium systems. The developed TimberCW is an innovative structurally glazed curtain wall system entirely comprised of laminated timber profiles incorporated in a fully prefabricated unitised curtain wall design, where glass panes are bonded by the structural silicone to timber frames. While most current timber curtain wall systems are stick designs, combined with aluminium elements, this new concept introduces timber split mullions and entirely eliminates aluminium structural members, whilst maintaining high weathertightness performance. In order to retain thin cross sections, as they are common for aluminium design, specialised corner connections in timber frame and stainless-steel bracketry has been developed and laboratory tested. Comparative energy efficiency analysis and condensation risk assessment of the TimberCW vs fully unitised aluminium systems of identical overall geometry and structural performance are presented. Full scale laboratory testing has been undertaken and certification obtained, proving the TimberCW concept suitable for project application.